The influence of surface adsorption on microbubble dynamics. - Stride, E (2008)
In a pure liquid, the behaviour of a gas or vapour microbubble is determined primarily by its size, the ambient pressure and the properties of the surrounding liquid. In practice, however, adsorption of a dissolved substance from the surrounding liquid onto the microbubble surface will often take place, producing a thin coating which can significantly affect both the microbubble's stability and its dynamic response. This can have important implications in a wide range of applications, including underwater acoustics, cavitation detection, medical imaging and drug delivery. The aim of this paper is to review the existing theoretical treatments of coated microbubbles and to present and discuss some recent developments. It will be shown that the presence of the coating can substantially modify the amplitude of microbubble volumetric oscillation, resonance characteristics and relative amplitude in tension and compression. Finally, the need for improved understanding of the dynamic behaviour of surface coatings at high frequencies will be discussed.